A Numerical study of Two-Phase flow through a Rectangular Duct with a Convergence Ribs - S.Al-Turaihi, Riyadh.; Sahi Shareef, Abbas; Abdalaimma, Ali (International Journal of Engineering and Technology, 2018)
Two-phase flow in ribbed convergent rectangular upward vertical duct was studied.Water and air were usedas materials for two-phase. Numerical studies have been performed to test the influence of increased air and water discharges on the pressure profile and pressure drop through the convergent section, as the effect of increasing the convergent angle on the pressure difference across the convergent section was studied. Water inlet discharges used were between (5-20 L/min), and air discharges were between (5.833-16.666 L/min). Two test channels with convergent angles (10 and 15 degrees) were used. Computational fluid dynamics for a three-dimensional model was simulated with ANSYS fluent 18 depending on the boundary condition and governed by equations of Eulerian multiphase flow model. The results indicated that the pressure along the test channel raises as water and air discharge rise. It was observedtoo the pressure drop increases with the increase of the convergence angle.